Japanese Propaganda through Songs in Djawa Baroe Magazine - Aufy, Kiky; A, Moh. Gandhi (Universitas Airlangga, 2022)
Djawa Baroe magazine played a crucial role as a propaganda tool for Japan during the occupation of Indonesia from 1943 to 1945. Propaganda was practiced through literary content, visuals, caricatures, and other forms of media. This study aims to analyze the titles and themes of songs in Djawa Baroe used as propaganda tools by the Japanese to mobilize the Indonesian population during the occupation from 1943 to 1945. A quantitative approach with descriptive analysis was used to examine the propaganda songs in Djawa Baroe (1943-1945). Primary data in the form of song lyrics were obtained from the Digital Library of Leiden University, Netherlands, with a total of 43 songs. The analysis shows that the songs in Djawa Baroe were used to mobilize the Indonesian population with themes that supported Japanese interests. The most dominant theme was nationalism (32.6%), followed by themes of work enthusiasm (14%), pride and Japanese nationalism (11.6%), Asian unity (11.6%), children's education (9.3%), maritime strength (7%), social solidarity (4.7%), saving (2.3%), and victory (2.3%). Initially, the songs reinforced military strength and patriotism, but as the war progressed, the focus of theme shifted to mobilizing human and economic resources and maintaining morale amid Japan's increasing desperation in World War II.